Hepatoprotective Effects of Indole, a Gut Microbial Metabolite, in Leptin-Deficient Obese Mice. Issue 6 (10th March 2021) - Knudsen, Christelle; Neyrinck, Audrey M; Leyrolle, Quentin; Baldin, Pamela; Leclercq, Sophie; Rodriguez, Julie; Beaumont, Martin; Cani, Patrice D; Bindels, Laure B; Lanthier, Nicolas; Delzenne, Nathalie M
ABSTRACT: Background: The gut microbiota plays a role in the occurrence of nonalcoholic fatty liver disease (NAFLD), notably through the production of bioactive metabolites. Indole, a bacterial metabolite of tryptophan, has been proposed as a pivotal metabolite modulating inflammation, metabolism, and behavior. Objectives: The aim of our study was to mimic an upregulation of intestinal bacterial indole production and to evaluate its potential effect in vivo in 2 models of NAFLD. Methods: Eight-week-old leptin-deficient male ob/ob compared with control ob/+ mice (experiment 1), and 4–5-wk-old C57BL/6JRj male mice fed a low-fat (LF, 10 kJ%) compared with a high-fat (HF, 60 kJ%) diet (experiment 2), were given plain water or water supplemented with a physiological dose of indole (0.5 mM, n ≥6/group) for 3 wk and 3 d, respectively. The effect of the treatments on the liver, intestine, adipose tissue, brain, and behavior was assessed. Results: Indole reduced hepatic expression of genes involved in inflammation [C-C motif chemokine ligand 2 ( Ccl2 ), C-X-C motif chemokine ligand 2 ( Cxcl2 ); 3.3- compared with 5.0-fold, and 2.4- compared with 3.3-fold of control ob /+ mice, respectively, P < 0.05], and in macrophage activation [ Cd68, integrin subunit α X ( Itgax ); 2.1- compared with 2.5-fold, and 5.0- compared with 6.4-fold of control ob /+ mice, respectively, P < 0.01] as well as markers of hepatic damage (alaninine aminotransferase; −32%, P < 0.001) regardless of genotype in experiment 1. Indole had no effect on hepatic inflammation in mice fed the LF or HF diet in experiment 2. Indole did not change hepatic lipid content, anxiety-like behavior, or inflammation in the ileum, adipose tissue, and brain in experiment 1. Conclusions: Our results support the efficacy of indole to reduce hepatic damage and associated inflammatory response and macrophage activation in ob/ob mice. These modifications appear to be attributable to direct effects of indole on the liver, rather than through effects on the adipose tissue or intestinal barrier.